A Small World : Smart Houses and the Dream of the Perfect Day - Heckman, Davin, 1975- (Book collections on Project MUSE., 2008)
A look at how domestic technologies that free people to enjoy leisure time in the home have come to be understood as necessary parts of everyday life.